Analysis of the Validity of the Content of Daily Test Instruments in Science Subjects in Grade V of Kromong State Elementary School - Parmi; Sa’idatud Daroini; Benny Chandra Nahera; Muhammad Na’am; Nataniel Ampung; Nensy Megawati Simanjuntak (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the content validity of the daily test instrument for the Natural and Social Sciences (IPAS) subject for fifth graders at Kromong Public Elementary School. Content validity is a fundamental aspect in the development of evaluation instruments, as it ensures that each item truly represents the basic competencies and learning indicators to be measured. This study used a quantitative descriptive approach involving three validators consisting of an IPAS material expert, an educational evaluation expert, and a senior teacher practitioner. The validated instrument consisted of eight descriptive questions on the theme "Living Things and Their Environment". The assessment was carried out using a four-point Likert scale and analyzed using the Aiken's V index to measure the level of agreement between validators regarding the suitability of the items. The analysis results showed that six of the eight items were in the high category with V values between 0.89 and 1.00, while the other two items obtained the medium category with V values of 0.78. The overall average Aiken's V value was 0.89, which indicates that the instrument has high content validity and is suitable for use in learning evaluation. These findings confirm that the cross-competency expert review-based validation process plays a significant role in ensuring the instrument's quality. However, some items require revision in terms of construction and language to improve clarity and understanding for elementary school students. Overall, the instrument can be used as a daily assessment tool with minor improvements to certain items.